2000
DOI: 10.1179/096797800680839
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation mechanism of MgO–C in air at various temperatures

Abstract: During charging, tapping, hot repairing, and idling, the refractory lining also comes into direct contact with the air. Oxidation of MgO-C refractories containing 20 wt-% At the face opposite the hot face of the refractories, the graphite was conducted by measuring the weight loss temperature is low and the face may also come into contact at regular intervals at various temperatures from 800 with air which comes through cracks, crevices, etc. Besides to 1600°C in air. T he rate of decarburisation increased dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 3 publications
3
38
0
Order By: Relevance
“…Hence, it is of great importance to obtain knowledge about the SEN's behaviour during the preheating process. Previous studies have shown that all RBMs that contain graphite have a high probability to be decarburised during the preheating operation, which is due to an increased oxygen activity near the inner wall of the refractory [8][9][10][11]. Here, it should be noted that RBMs normally contains about 5 to 35 wt-% graphite.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, it is of great importance to obtain knowledge about the SEN's behaviour during the preheating process. Previous studies have shown that all RBMs that contain graphite have a high probability to be decarburised during the preheating operation, which is due to an increased oxygen activity near the inner wall of the refractory [8][9][10][11]. Here, it should be noted that RBMs normally contains about 5 to 35 wt-% graphite.…”
Section: Introductionmentioning
confidence: 99%
“…This was done, according to reactions (1)- (3) and with the assumption that the activity of carbon equal to unity. Since the major constituents of Al 2 O 3 -C SEN are Al 2 O 3 and C the direct oxidation of graphite reactions that could take place during the preheating process are as follows [8][9][10][11]16]: …”
Section: The Influence Of Preheating Parameters On Decarburisationmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, may lead to volume expansion and cracking of the refractory bulk. 3) .................... (2) .... (3) Sunayama et al 4) have investigated the influence of aluminum additions on the oxidation rate of Magnesia/ graphite refractory, which showed a slight improvement of the oxidation resistance at temperatures below 1 823 K. Wang et al 5) have investigated the influence of Al 8 B 4 C 7 additions on the decarburization resistance of magnesia/ graphite refractory. In addition, Gokce et al 3) have evaluated the effects of various antioxidants such as Si, Al, B 4 C and SiC on the decarburization resistance of magnesia/ graphite refractory.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, graphite oxidation starts at 873-973 K in air to form carbon monoxide or carbon dioxide. 2) .............. (1) A method to inhibit the decarburization of Al 2 O 3 -C refractories is the addition of so-called antioxidants. An antioxidant is an element or a compound with a high oxidation affinity.…”
Section: Introductionmentioning
confidence: 99%